Interactive effects of benthivorous fish disturbance and ammonium loading on two submersed macrophytes of contrasting growth forms based on a mesocosm study - Qing Yu; Qing Yu; Haijun Wang; Haijun Wang; Miao Liu; Chao Xu; Yu Ma; Yu Ma; Weihua Guo; Erik Jeppesen; Erik Jeppesen; Erik Jeppesen; et al. (Frontiers in Environmental Science, 2022)
Benthivorous fish disturbance and nitrogen loading are two important factors that influence the community structure of submersed macrophytes, but their interactive effect is not well elucidated. We conducted an outdoor mesocosm experiment to examine the individual and combined effects of these two factors on the growth of two submersed macrophytes of different growth forms, i.e., the rosette-forming Vallisneria natans and the canopy-forming Myriophyllum spicatum. The treatments involved two levels of fish (Carassius auratus) disturbance crossed with two levels (0 and 12 g NH4Cl per month) of ammonium (NH4+-N) loading. For M. spicatum, we found that maximum height (MH) was reduced by 30.7%, 26.4%, and 51.0% in fish addition alone (F) and nitrogen addition treatments (N, F + N), respectively, compared with the control (C) treatment. The density of M. spicatum declined by 20%, 62% and 68.8% in the F, N and F + N treatment. The above-ground biomass (AGB) of M. spicatum respectively reduced by 56.7%, 94%, and 96.5% in the F, N and F + N treatments, and the roots/shoots ratio (R/S) increased by 114%, and 176% in N and N + F treatments, respectively. Regarding V. natans, only the MH in the N treatment was reduced (71.9%), and the density exhibited a reduction of 59.1% and 64.5% in the N and F + N treatments, respectively. The AGB of V. natans was significantly lower in the N (90.3%) and N + F (78.4%) treatments compared with the C treatment, while increased by 60.3% in F treatment. The R/S of V. natans increased by 227%, and 74.4% in the N and F + N treatments compared with the C treatment. The interactive effect of fish disturbance and high N on MH and AGB of V. natans and density of M. spicatum were antagonistic. However, the interactive effect on density and BGB of V. natans and AGB of M. spicatum were negatively synergistic. Moreover, fish activity significantly increased the concentration of total suspended solids (TSS) in the water, while total nitrogen (TN), ammonium, total phosphorus (TP), light, pH and salinity were unaffected. When fish and nitrogen were combined, TN, TP, TSS and salinity increased significantly, while pH decreased. Our study reveals that the interactive effects of fish disturbance and high N are synergistic and/or antagonistic, suggesting that the same stressor interaction may vary from synergistic to antagonistic depending on the response variables and growth forms of the macrophytes examined. Our study contributes to the understanding of how different factors can interact with each other and affect submersed macrophytes in aquatic ecosystems. This is timely and relevant knowledge, considering the range of multiple stressors involved in the decline of aquatic ecosystems worldwide at present.